2002
DOI: 10.1016/s0022-5347(05)65179-8
|View full text |Cite
|
Sign up to set email alerts
|

Holmium: Yag Laser Endoureterotomy For Ureterointestinal Strictures

Abstract: Ho:YAG laser endoureterotomy for ureterointestinal stricture disease is a minimally invasive endourological procedure that may provide more durable results than other modalities used for endoureterotomy. The Ho:YAG laser with its ability to cut tissue precisely and provide hemostasis combined with its versatility and compatibility with flexible endoscopes is an ideal instrument for safely performing endoureterotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Application of the Holmium laser has been used for the treatment of various urologic diseases such as BPH, urolithiasis including bladder calculi, urothelial carcinomas, and stricture disease of the urethra and ureter [26][27][28][29][30][31][32][33]. The Holmium laser is particularly useful when an obstructing prostate precludes access to the upper tract for the treatment of urinary calculi.…”
Section: Resultsmentioning
confidence: 99%
“…Application of the Holmium laser has been used for the treatment of various urologic diseases such as BPH, urolithiasis including bladder calculi, urothelial carcinomas, and stricture disease of the urethra and ureter [26][27][28][29][30][31][32][33]. The Holmium laser is particularly useful when an obstructing prostate precludes access to the upper tract for the treatment of urinary calculi.…”
Section: Resultsmentioning
confidence: 99%
“…Satisfactory success rates were later reported in somewhat larger series. Laven et al presented a series of 15 similarly treated patients with a success rate of 57% and mean followup of 20.5 months [26], whereas Watterson et al using the same method reported on 23 cases with a success rate of 71% in a mean follow-up interval of 22 months [27].…”
Section: Discussionmentioning
confidence: 99%
“…In a series of just three patients, Hibi et al 71 reported an 100% patency rate at a mean follow-up duration of 60.5 months after the procedure. In larger series, however, the overall success rate has been reported as being lower at 57% and 56% after a mean follow-up period of 20.5 months and 36 months respectively 73,74 .…”
Section: Endoureterotomymentioning
confidence: 91%